The Influence of Employee Competence and Use of Information Technology on Financial Accountability with the Success of Information Systems as Moderating Variables - Sukhemi; Marti Widya Sari (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: This study aims to determine the influence of employee competence and the use of information technology on financial accountability, and also the role of moderation in the success of the information system and how it impacts financial accountability vis-à-vis the use of information technology. Design/Methodology/Approach: This research was implemented with a casual setting for the Local Government Work Unit (LGWU) finance department employees in Bantul Regency. Samples were taken from 150 employees with accidental sampling. Data collection was carried out using questionnaires. Data analysis was performed using the PLS-SEM method. Research findings: Employee competence and the use of information systems have a positive and significant effect on financial accountability. The information systems’ success did not moderate the influence of information technology itself on financial accountability. Theoretical contribution/Originality: This research provides new insight into the role of moderation in the success of information systems on the influence of information technology on financial accountability. Practitioner/Policy implications: This study suggests that local governments can continue to improve employee competence through the use of information technology. One actionable way would be to make budget allocations for the maintenance and repair of the current information technology facilities and infrastructure. Research limitation/Implication: While previous research has focused on the use of information technology in enhancing financial accountability, these results show that the success of information system is a moderating predictor of accountability